STUDIES ON INCREASED PLANT POPULATION OF DIFFERENT VARIETIES OF MAIZE (Zea mays L) IN YOLA AND MUBI, ADAMAWA STATE, NIGERIA - Njodi, Mamudu; Toungos, Mohammed D.; Babayola, Mu’azu; Kashim, Hassan (International Journal of Research -GRANTHAALAYAH, 2019)
Field experiment were conducted at Yola and Mubi locations to study the effects of increased plant population of five (5) varieties of maize Viz: SAMMAZ 11, SAMMAZ 14, SAMMAZ 15, SAMMAZ 16, and SAMMAZ 17 on yield and yield component during the 2011 cropping season. The experimental design was a split plot design with maize varieties as the main plot treatments, while plant population, (53,333, 63,333, 80,000 and 106,666) as the sub-plot treatments. The treatment were replicated three (3) times. Characters measured included plant height, number of leaves per plant, number of days to 50% tasseling, number of day to 50 % silking, days to 95% maturity, number of ear per plant, stem diameter, length of ear, diameter of ear, number of grains per ear, 100 grain weight, number of grains per ear. Yield per plot and total grain yield per hectare. The result of the experiments showed that there was significant difference due to varietal effect in plant height at 3 WAS in Yola and at 7 WAS and 9 WAS in Mubi. Variety also affects days to 50% tasseling, days to 50% silking and days to 95% maturity at both locations. Variety also affects ear length at both locations. Interaction of variety and population affected harvest index in Mubi. Population significantly affected yield per plant, yield per plot, total grain yield per hectare in both locations. Combined analysis result showed highly significant effect due to location on plant height at 3 and 5 WAS and also due to variety. Location also affected number of leaves per plant significantly at 3WAS and highly significantly at 5, 7, 9 and 11 WAS. Varieties affected number of leaves per plant at 5 and 9 WAS and was highly significant at 11 WAS. Location and varieties affected days to 50% tasseling, days to 50 % silking and days to 95% maturity, while population only affected days to 50% silking. Diameter of ear and harvest index was highly significant by location and on number of grains per row. Varieties also showed significant differences in length of ear. Location affected straw weight per plant, while varieties affected yield per plant and yield per plot, weight of 100 grain yield and total grain yield per hectare was also highly significantly affected. Population affected yield per plant, especially the ones in Yola. Straw weight, total grain yield and weight of 100 grain were significantly affected. SAMMAZ 15 which gave a plant population of 106,666 ha-1 is recommended at both locations.